2021
DOI: 10.3390/polym13040549
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Dissolution of Argema mimosae Silk Fibroin and Fabrication of Films and Nanofibers

Abstract: Limited studies have been done on silk fibroins of wild silkworm species owing to their relative insolubility in many solvents. In this study, the solubility of Argema mimosae wild silk fibroin in different salts (LiBr, LiCl, Ca(NO3)2, and CaCl2) dissolved in formic acid under varying temperatures was investigated. The dissolution conditions under which the solubility was optimum were optimized using a central composite design approach. The optimum range for solvation of the fibroin were visualized using conto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…It is reported that to obtain silk powder with a particle size between 2–3 μm requires long milling times, and harsh pre-treatment processes must be employed in addition to the long milling times of up to 40 hrs [ 28 ]. While the powder still showed large aggregates, in the current study, however, the preparation of the silk films was carried out under relatively mild conditions to preserve the integrity of the silk fibroin with a milling time of 90 min [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that to obtain silk powder with a particle size between 2–3 μm requires long milling times, and harsh pre-treatment processes must be employed in addition to the long milling times of up to 40 hrs [ 28 ]. While the powder still showed large aggregates, in the current study, however, the preparation of the silk films was carried out under relatively mild conditions to preserve the integrity of the silk fibroin with a milling time of 90 min [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A. mimosae cocoons were degummed in a two-step degumming process for 90 min at each time as described in [ 23 ]. The cocoons were firstly boiled in 0.025 mol dm −3 then in 0.01 mol dm −3 Na 2 CO 3 aqueous solutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lithium bromide was replaced with cheaper Ajisawa solution [12][13][14], formic acid as a solvent with lithium chloride and calcium chloride salts [15] for SF dissolution which was further processed into SF powder.…”
Section: Introductionmentioning
confidence: 99%
“…Silk degumming procedure: 5g of raw silk boiled in 0.02M Na 2 CO 3 solution for 30min, rinsed 3 times with distilled water and dried overnight in a fume hood leaving SF bres [4,14,15].…”
Section: Introductionmentioning
confidence: 99%